Kaptol - a centre on the periphery of the Hallstatt world - Potrebica, Hrvoje (Array, 2012)
Two necropolises and a fortified settlement discovered near the village of Kaptol in the Požega Valley (Croatia) form one of the most important Hallstatt complexes in this part of Europe. The importance of the large and prosperous settlement accompanied by elite burials with prestigious goods from distant areas is probably based on the transitional position of the Hallstatt centre in Kaptol within the communication network, which connected the Mediterranean cultural area with the rich seats of Hallstatt princes in Central Europe. An important role in this system was played by the Iron Age cultures of the Balkans and Pannonia, which were closely and directly connected with the centre at Kaptol. The paper presents the research of the necropolis at Gradci, where fourteen tumuli were excavated in the period between 2001 and 2010. The paper also briefly presents the results of a ground survey of the hillfort, which suggests a longer life span for the settlement and its possible continuity into the La Tène Period.